Analisis Line Balancing Dengan Metode Moodie Young Proses Produksi Pabrik Keripik Kreasi Lutvi Tuntungan 2 - Hutabarat, Yeheskiel; Munthe, Sirmas; Sutrisno, Sutrisno (Universitas Medan Area, 2023)
Kreasi Lutvi Tuntungan II Chips Factory is a cassava chips production company facing significant idle time issues at various workstations. Workstation 2 experiences idle times of 599.87 seconds, 302.19 seconds, and 894.88 seconds. Workstation 3 encounters idle times of 1171 seconds and 138.75 seconds, while Workstation 4 has idle times of 625.56 seconds and 900.48 seconds. These idle times result from substantial disparities between the cycle times in the production line and workstation times. This study uses the Moodie Young method to assess the impact of workstations and idle time on the production line balance at Kreasi Lutvi Tuntungan 2 Chips Factory. The research investigates workstations and idle times to identify congestion and assess production line balance. The study outputs include the production line balance, represented by Balance Delay, Line Efficiency, and Smoothness Index, to determine the overall balance of the production line. The findings indicate suboptimal line efficiency on the actual line, with 4 workstations and 8 work elements achieving a line efficiency of 83%, a Balance Delay of 11.42%, and a Smoothness Index of 1195.85. In contrast, applying the Moodie-Young method results in improved line efficiency at 73.77%, a reduced Balance Delay of 22.06%, and an enhanced Smooth Index of 1798.85. This demonstrates that the Moodie Young method provides a more optimal level of line balancing compared to the existing production line at Kreasi Lutvi Tuntungan 2 Chips Factory.